Cotton fabric decorated with manganese oxide nanorods as a supercapacitive flexible electrode for wearable electronics - Samuel, Edmund; Joshi, Bhavana; Kim, Yongil; Park, Chanwoo; Aldalbahi, Ali; El-Newehy, Mohamed; Lee, Hae-Seok; Yoon, Sam S. (Applied Surface Science, 2021)
We present the fabrication (using a hydrothermal process) and the properties of wearable fabrics decorated with ultrathin manganese oxide (MnO2) nanorods for supercapacitor applications. The superior mechanical durability of the supercapacitor was confirmed by cyclic voltammetry (CV) curves, which showed little change during 1000 bending cycles. The pseudocapacitive properties of the ultrathin MnO2 nanorods were confirmed by recording the CV curves at various scan rates. The galvanostatic charge-discharge curves at various specific currents confirmed the pseudocapacitance of MnO2. The ultrathin MnO2 nanorods exhibited a superior capacitance of 508 F.g(-1) and an energy density of 35.3 Wh.kg(-1). The MnO2 electrode with optimal properties demonstrated stable long-term cycling performance with 90% retention after 10,000 galvanostatic cycles.
Keywords: Cotton fabric; Manganese oxide; Ultrafine nanostructures; Wearable supercapacitors